Self-monitoring of Blood Pressure: Awareness, Practice, Perceived Barriers and Associated Sociodemographic Factors Among Adult Hypertensives Attending a Tertiary Hospital in South-South Nigeria - Ejiroghene Martha Umuerri; Ehimwenma Judith Ogbemudia; Patrick Oyibo (International Journal of the Cardiovascular Academy, 2023)

(untitled)
Background and Aim:Self-monitoring of blood pressure (SMBP) is helpful in blood pressure (BP) status categorization and emerging evidence shows its beneficial impact on BP control. The study assessed the awareness and practice of SMBP and its associated sociodemographic factors among adult hypertensives in Southern Nigeria.Materials and Methods:The study was cross-sectional and questionnaire based. Eligible adult hypertensive patients attending a tertiary hospital in South-South Nigeria were randomly recruited from the cardiology clinic over one year.Results:Of the 364 hypertensive adults studied, the mean (± standard deviation) age was 59.34 (±14,308) years, males (192, 52.7%) and urban dwellers (273, 75%). A total of 287 (78.8%) were aware of SMBP, and 240 (65.9%) practiced it. Most (75, 60.5%) of the respondents who did not practice SMBP had no specific reason not to. Of the respondents who practiced SMBP, 226 (94.2%) owned a BP monitoring device, and 135 (56.3%) kept records of their BP readings, out of which 83% (112/135) cross-checked with clinic readings. The practice of SMBP was significantly associated with marital status (P = 0.038), education (P < 0.001), residence (P = 0.011), average monthly income (P = 0.020), and access to healthcare insurance (P = 0.042) but not with age, sex, and occupation.Conclusion:The awareness and practice of SMBP were high in this study. However, almost half of the respondents who practiced SMBP neither kept records nor cross-checked home BP with clinic readings, thus limiting the added clinical support offered by SMBP. Healthcare providers must continue educating patients to maximize the benefits of SMBP.